Behavior of hybrid thermosensitive nanosystem dextran-graft-PNIPAM/gold nanoparticles: characterization within LCTS - Kutsevol, N.; Glamazda, A.; Chumachenko, V.; Harahuts, Yu; Stepanian, S. G.; Plokhotnichenko, A. M.; Karachevtsev, V. A. (Journal of nanoparticle research : an interdisciplinary forum for nanoscale science and technology, 2018)
Thermally responsive polymers based on poly (N-isopropylacrylamide) (PNIPAM) with lower critical solution temperature (LCST) in the region of physiological temperatures become a subject of a study as promising material for biomedical application. In the present work, the star-like dextran-graft-PNIPAM with incorporated gold nanoparticles (AuNPs) in water suspension were studied by quasi-elastic light scattering (QELS), transmission electron microscopy (TEM), and spectroscopic methods in the temperature range around LCST. The analysis of QELS results revealed the individual polymer macromolecules with incorporated inside AuNPs and their aggregates, which demonstrate the LCST near 34 °C with the collapse of individual macromolecules and polymer aggregates too. The absorption spectroscopy measurements showed that the polymer structure is reversible at LCST and heating of polymer/AuNP nanosystems from room temperatures to LCTS does not accompany with a release of AuNPs from the polymer matrix. Raman spectra of nanohybrids were measured below and above LCTS and analyzed in details by employing DFT calculations. Two intense bands in the region 50–300-cm −1 region were observed for the first time. They were assigned to the stretching vibrations of Au-Au and Au-O (NIPAM) bonds. The presented work shows that the synthesized polymer with AuNPs has high stability going through LCST encouraging their use as a perspective system for drug delivery strategy. Graphical abstract